Desarrollo de una aplicación web para programa de salud materno neonatal de la Coordinación Zonal 3 – Salud. - Cusquillo Quispillo, Marisela Jazmin (2024)
Presently, there is a notable scarcity of web applications that facilitate the registration of compliance with quality standards in maternal and neonatal health at the national level. This dearth is a pressing issue, as the content provided by various web applications may raise concerns about its quality, security, breadth of information, and practical relevance for truly effective prevention and health promotion. Our research aimed not just to develop a web application for the maternal-neonatal health program, but to fill a crucial gap in the healthcare system. This application would allow for efficient tracking of compliance with maternal-neonatal standards. We utilized free software tools such as PostgreSQL, Node.js, and Angular to implement the website. We also adopted the Scrum methodology, an agile software development approach that allows for adaptation to new changes and, most importantly, fosters organized collaboration as a team. Furthermore, to ensure the quality of the web application, we conducted a thorough evaluation using surveys as a data collection technique. These surveys were applied to end users, and the usability was evaluated according to the stringent criteria established by the ISO/IEC 25010 standard. This comprehensive evaluation considered criteria such as recognizability of suitability, learning, operability, or ability to be used, protection against user errors, and aesthetics. This rigorous evaluation process underscores our commitment to delivering a reliable and user-friendly web application. Based on the results obtained, it was evident that the web application meets all the usability criteria mentioned above, obtaining the following results: recognizability of the suitability (96.97%), learning (95.45%), operability or ability to be used (96.21 %), protection against user errors (94.70%) and aesthetics (96.97%), which demonstrates that the web application is a valuable tool that allows optimizing the monitoring process of maternal and neonatal quality indicators.